Diseño de una electrolinera en la parroquia Dayuma provincia de Orellana - Chin Estrella, Jonathan Mauricio (2024)
The trend towards renewable energy sources and sustainable transport is becoming increasingly common globally, in response to climate change and the need to reduce greenhouse gas emissions. In this context, the present project focuses on the design and development of a charging station for electric vehicles in Dayuma parish, taking advantage of the existing electricity grid. The approach of this document is aimed at directly integrating the charging system with the local electricity infrastructure, which facilitates its implementation and accessibility. The methodology employed includes a detailed analysis of the electricity demand to be supplied in the area as well as an economic feasibility. This study takes into account the evaluation of the electrical system, shielding and grounding system as well as initial investment costs, operation of the charging system. A comprehensive technical design was carried out including the selection of charging technologies, the estimation of the capacity needed to meet future demand for electric vehicles, and the planning of the physical infrastructure of the charging station. It has been concluded that the implementation of a grid-connected electric vehicle charging station in Dayuma is technically feasible and in some cases economically sustainable. Key challenges and opportunities were identified— including the need to upgrade the local electricity infrastructure to support additional charging and the possibility of incentivizing the uptake of electric vehicles in the region through the provision of accessible and efficient charging services.